1988
DOI: 10.3109/00016488809119457
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus Medical Treatment of Nasal Polyps

Abstract: A randomized comparison of the usual surgical removal of nasal polyps versus systemic steroid treatment was performed in 53 patients. In all, continuous topical steroid treatment was given during the one year period of observation. In both groups the initial treatment resulted in a continuous increase in mean nasal expiratory peak flow as well as in the sense of smell; these two parameters showed a temporary statistically significant difference in favour of the medically treated group. In general though, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 2 publications
0
64
0
1
Order By: Relevance
“…It is a simple non-invasive method requiring minimal patient cooperation. AR has been used in the pre and postopera- tive evaluation of rhinoplasties 16 , turbinoplasties and/or turbinectomies 17 , polypectomies 18 , adenoidectomies 19 , in assessing snorers and patients with obstructive sleep apnea syndrome 20 , choanal atresia 21 , subglottic stenosis 22 , and in children with chronic rhinitis 23 . This study was made to obtain measurable data on FESS, due to the lack of objective evaluation data in literature on the result of nasal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is a simple non-invasive method requiring minimal patient cooperation. AR has been used in the pre and postopera- tive evaluation of rhinoplasties 16 , turbinoplasties and/or turbinectomies 17 , polypectomies 18 , adenoidectomies 19 , in assessing snorers and patients with obstructive sleep apnea syndrome 20 , choanal atresia 21 , subglottic stenosis 22 , and in children with chronic rhinitis 23 . This study was made to obtain measurable data on FESS, due to the lack of objective evaluation data in literature on the result of nasal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Though, topical steroids fail in eliminating the polyp they reduce them in size. Systemic steroid therapy is equally effective as simple polypectomy and it may serve as "Medical Polypectomy" [4].…”
Section: Discussionmentioning
confidence: 99%
“…Many other researches have shown that medical and surgical treatments are equally effective in patient of CRS with polyposis. [15][16][17][18] In another study done by Ebba Heden Blomquist et al showed that medical treatment seems to be sufficient to treat most symptoms of nasal polyposis. 19 We saw that after 3 weeks patients on only medical treatment showed only 26.47% improvement in polyp size on nasal endoscopy but in subjective assessment (VAS), they showed 62.36% improvement.…”
Section: -12mentioning
confidence: 99%